Efficacy and safety of anti‐TNF therapy in elderly patients with inflammatory bowel disease. Issue 4 (24th June 2015) - Lobatón, T.; Ferrante, M.; Rutgeerts, P.; Ballet, V.; Van Assche, G.; Vermeire, S.
Summary Background The general increased life expectancy is reflected in the age of patients with inflammatory bowel disease (IBD). The knowledge about efficacy and safety of anti‐tumour necrosis factor (TNF) therapy in elderly is scarce and conflicting. Aim To assess the efficacy and safety of anti‐TNF therapy in elderly patients taking into account eventual comorbidity. Methods Observational and retrospective single‐centred study where 66 IBD patients initiating anti‐TNF treatment at age ≥65 years (cases: ≥65 anti‐TNF) were compared with 112 IBD patients initiating anti‐TNF <65 years (controls <65 anti‐TNF) and 61 anti‐TNF naïve IBD patients treated with immunosuppressants (IMS) and/or corticosteroids (CS) ≥65 years (controls ≥65 IMS/CS). Controls were matched to cases for IBD type, follow‐up, disease duration and anti‐TNF type. Comorbidity was assessed by using the Charlson Comorbidity Index (CCI). Both efficacy and safety of treatment were adjusted for comorbidity. Results The short‐term clinical response to anti‐TNF at 10 weeks was significantly lower in cases: ≥65 anti‐TNF (68% vs. 89%; P < 0.001), whereas at ≥6 months, differences were not significant (79.5% vs. 82.8%; P = 0.639). The risk for any severe adverse events was higher in cases: ≥65 anti‐TNF than in controls <65 anti‐TNF (RR = 4.7; P < 0.001) or controls ≥65 IMS/CS (RR = 3.09; P = 0.0008). Age older than 65 and CCI > 0 were independent risk factors for malignancy and mortality regardless of the medication. Conclusion Elderly patients treated with anti‐TNF have a lower rate of short‐term clinical response and a higher rate of severe adverse events than the younger patients under the same treatment.